Gold–palladium core@shell nanoalloys: experiments and simulations - Spitale, Ana; Perez, M. A.; Mejía Rosales, Sergio; Yacamán, Miguel José; Mariscal, Marcelo M. (Royal Society of Chemistry, 2015)
In this work, we report a facile synthesis route, structural characterization, and full atomistic simulations of gold–palladium nanoalloys. Through aberration corrected-STEM, UV-vis spectroscopy and EDS chemical analysis, we were able to determine that Au(core)–Pd(shell) bimetallic nanoparticles were formed. Using different computational approaches, we were capable of establishing how the size of the core and the thickness of the shell will affect the thermodynamic stability of several core–shell nanoalloys. Finally, grand canonical simulations using different sampling procedures were used to study the growth mechanism of Pd atoms on Au seeds of different shapes.